Археологические раскопки в Триалети. К истории грузинских племен во II тысячелетии до н.э. - Джапаридзе, О. M. (1969)
Džaparidze = Japaridze, O. M.; Archaeological Excavations in Trialeti. On the History of Georgian Tribes in the Second Millennium B.C.; ausführliche russ. und engl. Résumés.